2008
DOI: 10.1210/jc.2008-1528
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Screening for Thyroid Carcinoma in Childhood Cancer Survivors: A Case Series

Abstract: Although ultrasound screening for thyroid cancer in the general population is not cost effective and could lead to unnecessary surgery, due to false positives, we believe that in childhood cancer survivors who received radiotherapy involving the head, neck, or upper thorax, it would be worthwhile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 15 publications
2
29
1
4
Order By: Relevance
“…This subtype is the most frequent one, not only in the general population, but also following treatment for childhood malignancy. 11,13,37,38,40,41 Some authors found that being less than 10 years of age was associated with an increased risk of thyroid cancer, 11,13,38 although we did not find similar results. In contrast, we confirmed that women are at an increased risk of developing thyroid cancer (HR=4.74; P=0.002), which has been suggested by other studies 13 and observed in the general population.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…This subtype is the most frequent one, not only in the general population, but also following treatment for childhood malignancy. 11,13,37,38,40,41 Some authors found that being less than 10 years of age was associated with an increased risk of thyroid cancer, 11,13,38 although we did not find similar results. In contrast, we confirmed that women are at an increased risk of developing thyroid cancer (HR=4.74; P=0.002), which has been suggested by other studies 13 and observed in the general population.…”
Section: Discussioncontrasting
confidence: 95%
“…36 Many previous studies have focused on thyroid cancer after treatment for childhood cancer. 13,30,[37][38][39] The reported prevalences varied, which may be due to several factors, e.g., the studies were frequently retrospective, based on questionnaires, or included small numbers of patients. In contrast, our study was prospective and included a large number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thyroid carcinoma has been sporadically reported after latency periods of between 5 years and up to 15 or 30 years after exposure, depending on the study (4,49,50). With the increasing use of ultrasound scans and FNAB, thyroid carcinoma tends to be diagnosed very accurately at early stages (51). Only two other retrospective studies reported the results of ultrasound examinations for the detection of thyroid nodules and/or carcinoma during the follow-up of patients receiving TBI as part of conditioning regimens for HSCT during childhood (22,24).…”
Section: Discussionmentioning
confidence: 99%